Demography and Etiology of Congenital Cataract in a Tertiary Eye Centre of Kathmandu, Nepal (Health Renaissance, 2015)
Background: Congenital Cataract is the most important cause of treatable childhood blindness. Rubella is one of the major causes of preventable disease in many countries. There are scanty reports on congenital cataract in Nepal. Objective: To find out the demographic and etiological factors of congenital cataract in children. Method: In a hospital based cross sectional study, 46 children with congenital cataract were evaluated to find out morphology of cataract, laterality, associated ocular and systemic abnormality, visual status and etiology of cataract. Assessment included antenatal, birth and neonatal history, a detailed eye examination in slit lamp or the operating microscope under general anaesthesia, serum serology for TORCH infections, random blood sugar, urine reducing substance and thyroid profile. Result: Among 46 children with congenital cataract, 76.1% children presented before 5 years of age and 78.2% had bilateral onset. Male to female ratio was 1.3:1. Most of the children were legally blind (79.3%) in cataractous eye. Family history of congenital cataract was present in 15.2% cases. The most common mode of presentation was leukocoria in 91.3%. Microcornea (28.3%), resolved uveitis (13.0%), and iris atrophy (8.7%) were the most common ocular associations. Delayed developmental milestone (21.7%) and cardiac anomalies (10.9%) were the most common systemic anomalies. Lamellar cataract (51.3%) was the most common morphology of cataracts observed. The maternal infection was the major cause of congenital cataract in 17.4% cases with predominantly rubella infection in 13% cases. Conclusion: Most of the children with cataract are legally blind. Maternal infection in the antenatal period is the major cause of congenital cataract.DOI: http://dx.doi.org/10.3126/hren.v12i1.11975  Health Renaissance 2014;12(1):3-10